Prácticas de enseñanza de lecto-escritura en el Primer año de educación General Básica de una Unidad Educativa ubicada en la PIO XII en la ciudad de Quito. - Paida Cañar, Angiee Milena (2016)
This titulation work will coordinate the pedagogical practices in First School Level in an Elementary school located in the South of Quito. The analysis of these problems were done by a study on the case, which allowed us to see the teaching practice and the management inside the classroom during the “teaching-learning” process in the “writing and reading” area. Considering the importance of the pedagogical practice and the contribution to the children’s developing; letting us to have a better understanding on the daily work for this Methodologic Process. The study of this case was done by a recording of the work and the observation cards, the same that allowed us collect the necessary information for the investigation and the analysis of the pedagogical practice, so we analyzed the way of teaching, what is teaching and the process of teaching. The final results of the pedagogical practices are not complied in the hour classes, noting that the pedagogics currents wich the school use for the education a repetitive process, where the active participation was not evident in the hour class.